Percutaneous dilatational tracheostomy for saturating influx of COVID-19 patients: Experience of military ENT physicians deployed in Mulhouse, France - Morvan, J.-B. (Eur Ann Otorhinolaryngol Head Neck Dis, 2020)
OBJECTIVES: The main objective was to demonstrate the feasibility of percutaneous tracheostomy performed under difficult conditions by military ENT physicians during their deployment in the military intensive care field hospital of the French Military Medical Service in Mulhouse to confront the exceptional COVID-19 pandemic. The secondary objective was to assess reliability and safety for patient and caregivers, with a risk of iatrogenic viral contamination. MATERIAL AND METHODS: A single-center retrospective study was conducted between March 25 and April 25, 2020, in 47 COVID-19 patients requiring prolonged mechanical ventilation. The inclusion criterion was having undergone percutaneous tracheostomy. RESULTS: Eighteen consecutively included patients had successfully undergone percutaneous tracheostomy despite unfavorable anatomical conditions (short neck: 83.3%, overweight or obese: 88.9%). Median time to completion was 11 days after intubation, with an average duration of 7 minutes. The procedure was technically compliant in 83.3% of cases, and considered easy (on self-assessment) in 72.2%, with 2 minor per-procedural complications. No crossover to surgery was required. There was only 1 major post-procedural complication (late hemorrhage). CONCLUSION: This study showed the feasibility of percutaneous tracheostomy by an ENT physician under COVID-19 biohazard conditions. The technique was fast, easy and safe and met safety requirements for patient and staff.